Holographic phase retrieval and reference design. (20th August 2019) - Barmherzig, David A; Sun, Ju; Li, Po-Nan; Lane, T J; Candès, Emmanuel J
Abstract: A general mathematical framework and recovery algorithm is presented for the holographic phase retrieval problem. In this problem, which arises in holographic coherent diffraction imaging, a 'reference' portion of the signal to be recovered via phase retrieval is a priori known from experimental design. A generic formula is also derived for the expected recovery error when the measurement data is corrupted by Poisson shot noise. This facilitates an optimization perspective towards reference design and analysis. We employ this optimization perspective towards quantifying the performance of various reference choices.